Optimization Studies of Iron Ore Tailings Powder and Natural Zeolite as Concrete Admixtures - Mahmoud Al-Khazaleh; P. Krishna Kumar (Salehan Institute of Higher Education, 2023)
The disposal of Iron ore tailings Powder (IP) is the primary concern for numerous steel industries. Similarly, natural zeolite, a significant by-product of volcanic eruptions, pollutes the environment to an extreme degree. This study investigates and implements the extensive use of IP and natural zeolite as admixtures in M20-grade concrete in order to address the challenges posed by IP and zeolite. By varying the admixture percentage, three distinct mix ratios were formed. First, sand was replaced by iron at concentrations of 5%, 10%, 15%, and 20%. Second, cement was replaced by zeolite at 5%, 10%, 15%, and 20%. In the final mixture, both sand and cement were substituted with iron ore powder and zeolite, respectively, at 5%, 10%, 15%, and 20%. Conplast SP 430, a water-reducing admixture, was used in all of the mixtures at 1% by weight of cement. The mechanical properties of concrete, including compressive strength, split tensile strength, and flexural strength, were studied. To evaluate the long-term properties of admixture-modified concrete, durability tests such as permeability tests, water absorption tests, rapid chloride attack tests, acid attack tests, and sulphate attack tests were conducted. In addition, slump cone tests and thermal conductivity tests were conducted on all the mix combinations to determine the changes in workability and thermal conductivity coefficient. The test results demonstrated that a mix containing 10% zeolite replaced with cement and 10% iron ore tailing powder replaced with sand has the highest performance in terms of strength and durability characteristics. The study also constructs a comparable cost estimate to ensure that its actual implementation is feasible. Doi: 10.28991/CEJ-2023-09-12-08 Full Text: PDF